Slavic borders at the turn of the 20th and 21st centuries. Language-society-culture-identity - Rutkovska , Kristina; Fedorovič, Irena; Dalecka, Teresa (Vilnius University Proceedings, 2022)
In theses, researchers from various scientific fields share their new research and their methods and application possibilities. Scientists write about linguistic and cultural relations between representatives of different nationalities, border issues, being in a multilingual and multicultural environment, and finally geopolitical changes that influence our lives. Theses also reflect the impact of the technological revolution on language and society, the emergence of new language forms and genres. The authors analyze the Internet and youth language, cultural homogenization and globalization. Attention is also drawn to rural and urban language differences, standard language and dialects, sociolects. Border regions are analyzed, which focus many identity and linguistic issues. Scientists also write about the dangers, because in the situation of multilingualism and multiculturalism there are processes that can lead to linguistic and cultural assimilation. Linguists also indicate tasks. One of them is the preparation of dialect dictionaries, flagged as an urgent task in view of the rapid disappearance of dialects or their evolution. In addition to traditional sources of material, researchers are exploring new sources such as posts on Instagram, videos on YouTube, podcasts or memes.
Keywords: Slavia; border; ethnolinguistics; sociolinguistics; dialect; identity